If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6 = 4u + 2 Reorder the terms: -6 = 2 + 4u Solving -6 = 2 + 4u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-4u' to each side of the equation. -6 + -4u = 2 + 4u + -4u Combine like terms: 4u + -4u = 0 -6 + -4u = 2 + 0 -6 + -4u = 2 Add '6' to each side of the equation. -6 + 6 + -4u = 2 + 6 Combine like terms: -6 + 6 = 0 0 + -4u = 2 + 6 -4u = 2 + 6 Combine like terms: 2 + 6 = 8 -4u = 8 Divide each side by '-4'. u = -2 Simplifying u = -2
| -32=3(x-8)-7x | | 8[x+7m]-3=-5 | | x^3-7x^2+13x-3=0 | | 2y^2+9=10y | | 8[x+7m]-3=5 | | 3(v-5)=4(2v-3) | | *-15=4 | | (2x-8)/(2x) | | 5[3+7m]+1=-51 | | 2x-8/2x | | 5[3+7m]+1=51 | | r^2+18r+14=0 | | 6x+4=-2x+37 | | 3+5[8-2x]=-63 | | -7t-(-7)*3+4t=3(7)+3t | | 3ln(9x)=9 | | 1/5*g=9-2/5*g | | 3+5[8-2x]=63 | | -x+3(5)=12 | | x^(2/3)+9x^(1/3)+14=0 | | -7/2y=28 | | -7(t-3)+4t=3(7+2t) | | 3y=51 | | -5/9x=-15 | | x+(x+5)=74 | | 95=5w | | 9,000,000+200,000x=500,000x | | 2x^2-27xy^2=0 | | 49=-7/6u | | 25=-5/3w | | 4x^(2/3)+5=21 | | 51=3u |